2017
DOI: 10.1017/s1743921317004549
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of radionuclides in 3D models of SN 1987A and Cas A

Abstract: Abstract. Fostered by the possibilities of multi-dimensional computational modeling, in particular the advent of three-dimensional (3D) simulations, our understanding of the neutrino-driven explosion mechanism of core-collapse supernovae (SNe) has experienced remarkable progress over the past decade. First self-consistent, first-principle models have shown successful explosions in 3D, and even failed cases may be cured by moderate changes of the microphysics inside the neutron star (NS), better grid resolution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
1
3
0
1
Order By: Relevance
“…From the neutron star kick inferred by the distribution of intermediate-mass elements (e.g., Katsuda et al 2018) and the redshifted 44 Ti spectrum (Boggs et al 2015), the direction of the compact object is predicted to be moving toward us and extending along the north-east direction in the sky projection (e.g., Janka et al 2017). The location of this blob is consistent with that prediction.…”
Section: The Blob: Gas and Dust Heated By The Compact Sourcesupporting
confidence: 65%
“…From the neutron star kick inferred by the distribution of intermediate-mass elements (e.g., Katsuda et al 2018) and the redshifted 44 Ti spectrum (Boggs et al 2015), the direction of the compact object is predicted to be moving toward us and extending along the north-east direction in the sky projection (e.g., Janka et al 2017). The location of this blob is consistent with that prediction.…”
Section: The Blob: Gas and Dust Heated By The Compact Sourcesupporting
confidence: 65%
“…Abellán et al (2017) find that none of the neutrino driven explosion models they compare fit all observations of SN 1987A, a conclusion that supports a similar earlier claim by Soker (2017). Soker (2017) compared the Fe structure of SN 1987A from Larsson et al (2016) with the numerical simulations by Wongwathanarat et al (2015) and concluded that the neutrino-driven explosion mechanism cannot account for the structure of the Fe/Si-bright regions of SN 1987A (but this is in dispute in the literature, e.g., Janka et al 2017). Namely, the numerical simulations of Wongwathanarat et al (2015) predict several narrow Fe-rich fingers while the observed Fe/Si-bright structure has two large regions.…”
Section: Introductionmentioning
confidence: 56%
“…This holds for the inner ejecta of CCSNe that have inhomogeneous structures of filaments, clumps, and rings of different heavy elements such as oxygen, silicon, sulfur, argon and iron. According to the delayed neutrino explosion mechanism of CCSNe, instabilities that inherently exist in this explosion mechanism cause these filamentary structures of the inner ejecta (e.g., Janka et al 2017;Wongwathanarat et al 2017;Gabler et al 2021;Sandoval et al 2021). According to the jittering jets explosion mechanism of CCSNe, both instabilities and jittering jets shape the ejecta (e.g., Papish & Soker 2014a;Papish et al 2015a;Gilkis & Soker 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Zwei große Emissionsmaxima mit Geschwindigkeiten um zirka 2300 km/s dominieren die stark asymmetrische Verteilung, was für einen starken Rückstoß des entstandenen Neutronensterns spricht. Rechts: Eisenverteilung in der 3D‐Simulation einer neutrinogetriebenen Explosion, die Ähnlichkeit mit der Supernova 1987A aufweist [27]. Der Innenbereich niedriger Geschwindigkeiten entlang der Sichtlinie ist ausgeschnitten, um den Blick zum Explosionszentrum freizugeben.…”
Section: Erfolgreiche Modelle Erklären Beobachtungenunclassified